Evaluation of antihypercholesterolemic effect using Memecylon edule Roxb. ethanolic extract in cholesterol-induced Swiss albino mice - Kuppusamy, Palaniselvam; Paul Raj, R.S. David; Ilavenil, Soundharrajan; Kaleeswaran, Balasubramanian; Govindan, Natanamurugaraj; Maniam, Gaanty Pragas; Ravikumar, Sivanesan (Elsevier, 2015)
Purpose/Aim: In the present study, we investigate the antihypercholesterolemic effect of the ethanolic extract of Memecylon edule in in vivo. Methods: Cholesterol (1%) -induced experimental groups were treated with 100 mg/kg and 200 mg/kg M. edule ethanolic extract. The study period of antihypercholesterolemia, the mice body weight, lipid profile, serum enzymes (such as superoxide dismutase, catalase, and glutathione peroxidase), liver marker enzyme, and histopathological study of liver tissues were examined. Results: The M. edule-treated groups have exhibited significant changes in total cholesterol, very-low-density lipoprotein, and low-density lipoprotein, and eventually increased the high-density-lipoprotein activity in serum. Also, it reduced the malondialdehyde level and increased the antioxidant-enzyme activities. The activity is mainly the presence of flavonoids, tannins, saponins, and glycosides in the ethanolic extract of M. edule. Conclusion; The M. edule extract contains a different class of secondary metabolites, which reduces the hypercholesterolemic condition in the experimental animal model. The results explored the M. edule extract as a potent drug for hypercholesterolemic condition.